2002
DOI: 10.1088/0953-8984/14/23/305
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties and viscosity of liquid CdTe-based alloys

Abstract: High-temperature measurements of the electrical conductivity σ(T), thermo-emf S(T) (in a range from the vicinity of the melting temperature, Tm = 1371 to 1600 K), and viscosity η(T) (from Tm to 1420 K) were performed for equiatomic liquid CdTe alloys and with admixtures of In, Ge, Sn. It was shown that all the compositions kept their semiconducting properties during transition from a solid to a liquid state. A gradual melt metallization has been observed in the course of further heating. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, the results of the electrical conductivity s(T) measurements of CdTe both doped by In, Ge, Sn, As [3][4][5] and undoped [2][3][4][5] as well as Cd 1 À x Zn x Te melts [6] were analyzed in purpose of their correspondence to the Arrhenius equation.…”
Section: Cdte-based Melts Electrical Conductivity and Compensation Efmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the results of the electrical conductivity s(T) measurements of CdTe both doped by In, Ge, Sn, As [3][4][5] and undoped [2][3][4][5] as well as Cd 1 À x Zn x Te melts [6] were analyzed in purpose of their correspondence to the Arrhenius equation.…”
Section: Cdte-based Melts Electrical Conductivity and Compensation Efmentioning
confidence: 99%
“…Various methods have been used today for investigation of the CdTe and CdZnTe melts transformation with increasing and decreasing temperature: electrical conductivity [1][2][3][4][5][6], thermo power [3,5], viscosity [7,8], differential thermal analysis [9][10][11][12] and others. It was shown that the crystals melting process occurs step-by-step with rapid transformation of creating structural units at certain temperatures [2,3,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the investigation of the features of the structural state of melts and interparticle interaction in them, indirect methods are frequently used, which are based on studying temperature and concentration dependences of structure-sensitive properties of a melt such as viscosity, density, electrical resistance, magnetic susceptibility [11,[20][21][22]. The existing data on the investigation of the properties of melts of the binary Al-R [23][24][25][26][27], ternary Al-TM-R [28][29][30] and more complex systems based on them [30][31][32] confirm the conclusion about the micro-heterogeneous structure of the melts.…”
Section: Introductionmentioning
confidence: 99%
“…19 This is in agreement with studies of kinematic viscosity, which has a maximum in the stoichiometric CdTe and decreases both in Cd-and in Te-enriched melt. 9,20 Ions tend to exist within the tetrahedral configuration with heterogeneous bonds in such a strained environment, which inevitably causes long-range correlations and, therefore, cluster formation. The ab-initio moleculardynamic simulations of liquid CdTe suppose that Te atoms form long helicon chains in the melt, 21 typical for pure liquid Te.…”
Section: Introductionmentioning
confidence: 99%